Pengaruh Tekanan, Kesempatan, Rasionalisasi dan Kemampuan Terhadap Academic Fraud pada Mahasiswa Program Studi Akuntansi Universitas Balikpapan - Lipo Andy William Oey; H. Hairul Anam; Ika Makherta S (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the Influence of Pressure, Opportunity, Rationalization and Ability on Academic Cheating. The sampling technique in this study uses purposive sampling. The data analysis techniques used in this study are Outer Model, Inner Model and Hypothesis Test using the WarpPLS 3 application. Based on the results of the research that has been carried out, it shows that Pressure and Rationalization have no effect on Academic Cheating, while Opportunity and Ability affect on Academic Cheating .